Impact of urban satellites in fast fashion last mile distribution. Issue 12 (2nd December 2022) - Alfieri, Arianna; De Marco, Alberto; Pastore, Erica
ABSTRACT: The paper addresses how urban satellites affect profit, based on inventory management policies and operational conditions. An Italian fast-fashion supply chain is used as case study. The case study aims at capturing the consumers' purchasing attitudes under order-and-wait sale scenarios. Discrete event simulation is used, and input data are fitted from the case study. Results show that urban satellites can decrease store inventory for on-shelf items, thus increasing lost demand and impacting on transportation costs. However, adding satellites allows to increase assortment through the available retail store space, thus attracting new customers, increasing sales and profit. The study eventually gives managerial implications for urban satellites on store floors space usage, assortment and distribution policies.